2020
DOI: 10.3390/diagnostics10030132
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of Cholangioscopy: Established and Investigational Uses of SpyGlass in Biliary and Pancreatic Disorders

Abstract: Direct visualization of bile and pancreatic duct pathology is proving to be beneficial in patients where previous techniques have failed. Recent advancements in technology and the development of the SpyGlass system have led to an increased use of cholangioscopy. It is already known that SpyGlass is beneficial in patients with difficult bile duct stones and indeterminate biliary lesions through the use of targeted lithotripsy and visually guided biopsy. Cholangioscopy allows the visualization of hidden stone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
(50 reference statements)
0
28
0
2
Order By: Relevance
“…The complication rate in this study was 20%. Previous studies found total complication rates of 7 to 13% for peroral cholangiopancreatoscopies [32][33][34]. In our study, patients underwent pancreatoscopy, and no cholangioscopies were performed.…”
Section: Discussionmentioning
confidence: 62%
“…The complication rate in this study was 20%. Previous studies found total complication rates of 7 to 13% for peroral cholangiopancreatoscopies [32][33][34]. In our study, patients underwent pancreatoscopy, and no cholangioscopies were performed.…”
Section: Discussionmentioning
confidence: 62%
“…We believe that this is due to the characteristics of this novel system: the inner catheter has a tapered shape and there is no difference in the outer diameter between the inner catheter and the outer sheath, which enables the system to pass through the biliary strictures smoothly and allows the biopsy forceps to easily and accurately reach the target site beyond the biliary strictures via the outer sheath, thus making it possible to evaluate the superficial extension of cancer cells in the peripheral bile duct (Video S2). In contrast, a cholangioscope may not be effective in evaluating such peripheral bile ducts because its non‐tapered form does not allow it to pass through the biliary stricture 25,26 . Furthermore, in mapping biopsies, care must be taken to avoid contamination of the cancer cells, which can cause incorrect assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This case shows the possibility of using lithotripsy with spyglass cholangioscopy as a potentially safer, non-invasive alternative to surgery in the treatment of refractory bile duct stones [ 13 , 14 ]. Furthermore, Spyglass cholangioscopy enables the endoscopist to directly visualize the bile duct for accurate diagnosis and treatment of pathology [ 13 , 15 ]. However, equipment availability and training requirements make its widespread use less feasible.…”
Section: Discussionmentioning
confidence: 99%